Evaluation of rational drug use of general practitioners' in management of elderly patients [Prati̇syen heki̇mleri̇n yaşlilarda akilci i̇laç kullanimi alişkanliklarinin deǧerlendi̇ri̇lmesi̇] - (:unkn) unknown (My University, 2001)
Rational drug use in elderly is of greater importance because of physiological, pharmacokinetic and pharmaco-dynamic changes and poor compliance. In the present study, it was planned to investigate whether general practitioners take the general principles of rational drug use into consideration while they manage their elder patients. One hundred sixty two patients were face-to-face interviewed and a total of 122 prescriptions given to these patients were analysed. The patient-interviews revealed that 75% of patients were not examined, 63% were not informed about their diagnosis, 77% were not give given any information and instructions about the use of drugs, and 91% were not told about non-drug treatment. Seventy% of the prescriptions were not written with a legible or decipherable hand-writing. The prescription analysis showed that drugs acting on cardiovascular system, including antihypertensives, were the most frequently prescribed drugs (28%), followed by analgesic/ antiinflammatory drugs (17%) and vitamin / mineral preparations (9%). Nonsteroidal anti-inflammatory drugs and penicillin+beta lactamase inhibitors were the most common analgesic (62%) and antibiotic choices (19%), respectively, which might be considered as an indicator of irrational prescribing habit. On the other hand, antihypertensive drug choices seemed to be rational. However, this might be because general practitioners usually repeat the prescriptions written by specialists rather than examining the patients themselves. In conclusion, it was shown that general practitioners do not fully apply the principles of rational drug use while managing their elder patients. This problem mignt be solved partly by continuous education of the physicians about this issue.
Keywords: Elderly; General Practitioners; Polypharmacy; Prescription; Rational Use of Drug